Subscapular arterial entrapment between two roots of median nerve with concurent higher division of radial nerve– a case report. - Naveen, K; Satheesha, NB; Ashwini, AP; Suhani, S; Mamatha, H (Department of Surgery, UKM Medical Centre, 2013)
Neurovascular variations in the axilla and the arm are quite common. Some of them are clinically significant and the knowledge about the same is handy during planning of a surgery in the region. We observed some neurovascular variations in the axilla and proximal part of the arm. The subscapular artery was sandwiched between the two roots of median nerve. It gave a common arterial trunk which divided into three branches; superior ulnar collateral artery, profunda brachii artery and a muscular branch. The radial nerve divided into its two terminal branches in the axilla. There is a possibility of compression of subscapular artery in this case as it passed between the two roots of median nerve.